PERILAKU KONSUMSI TABLET TAMBAH DARAH PADA REMAJA PUTRI - Wahyudi, Nanda (Balai Besar Pelatihan Kesehatan (BBPK) Makassar, 2023)
ABSTRACT Background Anemia is a body condition where the hemoglobin (Hb) level in red blood cells is lower than the standard it should be. Adolescent girls are said to be anemic if Hb <12 gr/dl. 1 in 5 teenagers in Indonesia suffers from anemia. Young women are advised to take blood supplement tablets to prevent anemia. The aim of this research is to determine the number of teenagers who actively consume blood supplement tablets in Tabumela Village, Tilango District, Gorontalo Regency. This research method is a descriptive observational study with a cross sectional design. Research time October 2023. Total population is 96 people, the total research sample is 83 young women. The sampling technique is purposive simple random sampling. Data analysis used univariate analysis of frequency distribution. Results: 72.3% of young women did not consume blood supplement tablets. Conclusion: Most young women do not take blood supplement tablets. It is recommended that similar research be carried out, namely research on the consumption behavior of female adolescent blood supplement tablets accompanied by examination of HB levels. Keywords : teenager, fe, consumption ABSTRAK Anemia adalah kondisi tubuh dimana kadar hemoglobin (Hb) di dalam sel darah merah lebih rendah dari standar yang seharusnya. Remaja putri dikatakan anemia jika Hb <12 gr/dl. 1 dari 5 remaja di Indonesia menderita anemia. Remaja putri dianjurkan untuk mengonsumsi tablet tambah darah untuk mencegah anemia. Tujuan penelitian ini adalah untuk mengetahui jumlah remaja yang aktif mengonsumsi tablet tambah darah di Desa Tabumela, Kecamatan Tilango, Kabupaten Gorontalo. Metode penelitian ini merupakan penelitian deskriptif observasional dengan pndekatan cross sectional. Waktu Penelitian Oktober 2023. Jumlah sampel adalah 83 orang remaja putri (total populasi). Teknik pengambilan sampel purposive simple random sampling. Analisis data menggunakan analisis univariat distribusi frekuensi. Hasil 72,3% remaja putri tidak mengonsumsi tablet tambah darah. Kesimpulan, Sebagian besar remaja putri tidak mengonsumsi tablet tambah darah. Disarankan agar melakukan penelitian serupa yaitu penelitian mengenai perilaku konsumsi tablet tambah darah remaja putri disertai pemeriksaan kadar HB. Kata kunci: remaja, fe, konsumsi